A literature review on the implementation of continuous improvement in the Indonesian manufacturing and service industries - Nindiani, Aina; Sulastri, Fitri; Suhara, Ade (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Organizations worldwide, including in Indonesia, must be adaptive by continuously making improvements, or continuous improvements, so that their business continues to run forever. This research aims to analyze the implementation of continuous improvement in Indonesia in the manufacturing and service industry sectors. The literature review was carried out using the keywords implementation of continuous improvement, application of kaizen, and the like in the Google Scholar database. This literature review intends to determine how the continuous improvement (CI) process is carried out in Indonesia and what results are achieved. CI implementation is carried out using various tools that improve the work system. The objective value of implementing continuous improvement is then synthesized in manufacturing and service industry studies. In the manufacturing industry, the objective values that can be drawn based on the study's results are increasing production efficiency, optimizing product quality, reducing production costs, increasing time-to-market speed, a culture of innovation, increasing employee involvement, and sustainability and competitiveness. Meanwhile, in the service industry, it is improving service quality, operational efficiency, service innovation, quality management system effectiveness, and competitive advantage.